Design Web-Based Information System of Tri Dharma Higher Education for Lecturer - Anastasia, Lenshy Aprisilia; Pinontoan, Benny; Latumakulita, Luther Alexander (Operations Research: International Conference Series, 2022)
Tri dharma of higher education consisting of education & teaching, research, and community service which must upheld by every lecturer at universities in Indonesia. Lecturer who has implemented the tri dharma of higher education need these tri dharma files for promotion and lecturer performance report to get allowance. It is important to have an online system to store those files. In this research we develop a web-based information system for processing lecturer tri dharma activities data using Rapid Application Development (RAD) Method which started from requirement planning, system design, and implementation.